Pediatrics massage evidence map - Priscilla Araújo Duprat de Britto Pereira; Carmem Veronica Mendes Abdala; Caio Fabio Portella; Ricardo Ghelman; Mariana Cabral Schveitzer (Elsevier, 2021)
Background: This evidence map describes Pediatrics Massage intervention research reporting health outcomes. Massage is a complementary therapy and can be defined as any form of systematic tactile stimulation by human hands, the type of massage typically used in pediatrics care is a gentle, slow stroking of each part of the body in turn. Methods: The evidence map is based on the 3iE evidence gap map methodology. We searched four electronic databases from inception to November 2019 and included systematic reviews and non-systematic reviews. Systematic reviews were analyzed based on AMSTAR 2. We used tableau to graphically display confidence level, number of reviews, outcomes and a broad estimate of effectiveness. Results: The map is based on 38 reviews. Most of the reviews were published in the last ten years. The Pediatrics Massage was the most researched intervention. Massage was evaluated as an intervention in several health outcomes, resulting in the following confidence levels: 11 high, 13 moderate and 14 low. Every outcome effect was classified: 6 as no effect; 1 mixed and 28 as positive. The outcomes were divided into four major groups: physical and metabolic effects; vitality, well-being and quality of life, mental health; and management. High quality studies presented no effect and positive effects, highlighting outcomes related to neuro-motor development (Badr et al., 2015; Bennett et al., 2013; Vickers et al., 2015), growth (Badr et al., 2015; Bennett et al., 2013; Vickers et al., 2015) and stress disorders (Bennett et al., 2013; Vickers et al., 2015). Conclusions: Pediatrics massage has been applied in different areas and these Evidence Gap Map provides an easy visualization of valuable information for patients, health practitioners and managers, in order to promote evidence-based complementary therapies.